2014
DOI: 10.1038/gt.2014.104
|View full text |Cite
|
Sign up to set email alerts
|

The Tol2 transposon system mediates the genetic engineering of T-cells with CD19-specific chimeric antigen receptors for B-cell malignancies

Abstract: Engineered T-cell therapy using a CD19-specific chimeric antigen receptor (CD19-CAR) is a promising strategy for the treatment of advanced B-cell malignancies. Gene transfer of CARs to T-cells has widely relied on retroviral vectors, but transposon-based gene transfer has recently emerged as a suitable nonviral method to mediate stable transgene expression. The advantages of transposon vectors compared with viral vectors include their simplicity and cost-effectiveness. We used the Tol2 transposon system to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Also, Tol2 vectors have been used for transfection of foreign DNAs into mammalian cells including ESCs, iPSCs and human lymphocytes [86, 93, 94]. In addition, Tol2 vectors with a fluorescent marker or a transcription activator such as rtTA have been introduced to chick and mouse embryos by electroporation to label and analyze specific cell types in vivo [95, 96].…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
“…Also, Tol2 vectors have been used for transfection of foreign DNAs into mammalian cells including ESCs, iPSCs and human lymphocytes [86, 93, 94]. In addition, Tol2 vectors with a fluorescent marker or a transcription activator such as rtTA have been introduced to chick and mouse embryos by electroporation to label and analyze specific cell types in vivo [95, 96].…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
“…136 Tol2-mediated CD19specific CAR expression in T-lymphocytes was recently demonstrated to suppress B cell lymphoma progression both in vitro and in vivo. 73 Comparative analysis indicated that PB was more robust than SB11 and Tol2 systems. 137 In vivo transposon delivery Transposon-mediated gene transfer has also been validated for in vivo transfection.…”
Section: Hscmentioning
confidence: 99%
“…70 Tol2 transposon is able to deliver a genetic cargo up to 10-11 kb in several mammalian cells without compromising transposition efficiency. [71][72][73][74] Moreover, the Tol2two-component system has been used successfully to generate transgenic animals such as mouse, chicken, frog, [75][76][77][78][79] and particularly zebrafish models. 72,77,80,81 Like SB and PB, the Tol2 system enables sustained transgene expression after gene delivery, thereby providing the advantage of being suitable vector for gene therapy 72,73 (Fig.…”
Section: Tol2mentioning
confidence: 99%
“…The potential for this risk arises from the random nature of integration into the host genome, although no instances of this occurring in clinical trials using CAR-T cells engineered through these methods have been reported. Alternatively, transposon-based systems are capable of delivering a larger payload (~100 kb), cost effective, scalable and potentially less immunogenic than viral vectors [220][221][222] . This approach requires delivery of plasmid DNA encoding the transgene and transposase components, which is most commonly achieved through electroporation 221 , a method that can be toxic to the cells and is not as efficient as viral-based delivery.…”
Section: Delivery Of Car Genesmentioning
confidence: 99%